2006
DOI: 10.1063/1.2405417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dual frequency on the plasma characteristics in an internal linear inductively coupled plasma source

Abstract: An internal-type linear inductive antenna, referred to as a “double comb-type antenna,” was used as a large area plasma source with a substrate size of 880×660mm2 (fourth generation glass size). The effects of the dual frequency (2 and 13.56MHz) radio frequency (rf) power to the antenna as well as the power ratio on the plasma characteristics were investigated. High-density plasma on the order of 1.7×1011cm−3 could be obtained with a dual frequency power of 5kW (13.56MHz) and 1kW (2MHz) at a pressure of 15mTor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Another possible reason is the higher power absorption at low (2 MHz) driving frequency. It is well known that ohmic heating in the plasma volume is proportional to the electric field strength which is inversely proportional to the driving frequency; 22 thus, a higher electric field is expected at 2 MHz driving frequency compared to 13.56 MHz, which produces a higher plasma density. Previously, in Ar discharge and in the same set-up, it was shown that a higher plasma density is produced by two antennae energized by 2 and 13.56 MHz when compared to a single coil energized by 13.56 MHz for the same total input power.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible reason is the higher power absorption at low (2 MHz) driving frequency. It is well known that ohmic heating in the plasma volume is proportional to the electric field strength which is inversely proportional to the driving frequency; 22 thus, a higher electric field is expected at 2 MHz driving frequency compared to 13.56 MHz, which produces a higher plasma density. Previously, in Ar discharge and in the same set-up, it was shown that a higher plasma density is produced by two antennae energized by 2 and 13.56 MHz when compared to a single coil energized by 13.56 MHz for the same total input power.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple antenna ICPs are proposed and designed in order to scale up the conventional single frequency ICPs for largearea device fabrication. [21][22][23] The rationale of multipleantenna ICPs is to increase the coil area by keeping the coil inductance low enough to enable efficient RF matching and uniform plasma over the large-area substrate size. Based on this concept, a dual-frequency (2/13.56 MHz), dual-antenna ICP (12 turn inner coil powered by 2 MHz and three turn outer coil powered by 13.56 MHz) has been designed.…”
Section: Introductionmentioning
confidence: 99%
“…This can result in intensive ion bombardment of the ICP source antenna causing erosion of the dielectric material on the antenna and contamination by the sputtered dielectric materials. In addition, non-uniform rf voltage developing along the long antenna caused by a standing wave effect may also deteriorate plasma uniformity over the substrate surface [8][9][10][11].…”
Section: Introductionmentioning
confidence: 97%
“…Many schemes, based on multiple frequencies, power splitting mechanism, pulse shape tailoring, and customized shape of bias power, have been proposed. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Recently, a new approach, based on using dual frequency and power splitting mechanism in ICP source, has been proposed to provide a good discharge uniformity and control on discharge parameters. 30,31 Pulsing the plasma source provides an added flexibility in controlling the discharge parameters and proves to be an important tool for tailoring discharge parameters specific to a particular application.…”
Section: Introductionmentioning
confidence: 99%